Rational use of agricultural lands: monitoring the humus balance across crop rotations - Zhygailo, T.; Chugai, A.; Zhygailo, O.; Tolmachova, A. (Land Management, Cadastre and Land Monitoring, 2025)
Sustainable land use cannot be achieved without deliberate efforts to preserve and restore soil fertility, with the humus status serving as its key indicator. The challenge of maintaining a stable humus balance has become particularly pressing under the dominance of short-rotation crop sequences in the agricultural practice of the Southern Steppe of Ukraine. The absence of systematic monitoring of soil organic matter complicates the prediction of agroecosystem productivity and threatens the degradation of chernozems, the country’s most valuable agricultural resource. This study aimed to assess the performance of different short-rotation crop rotations under conditions of complete fertilizer exclusion, to quantify their effects on the humus balance, and to identify the most suitable model for long-term land use. The methodological framework was based on humus balance calculations in a five-field rotation with winter rapeseed and sunflower, conducted during 2020–2024. The results indicated that technical crops generated a negative humus balance (–0.28 t/ha and –0.77 t/ha, respectively), with the most severe deficit observed after bare fallow (–1.46 t/ha). In contrast, cereals contributed to partial restoration of humus reserves (up to +0.21 t/ha and +0.08 t/ha), while the highest positive effect was obtained from green fallow (+1.14 t/ha). The overall balance per rotation amounted to –2.22 t/ha in the first sequence and +0.38 t/ha in the second. These findings highlight the importance of incorporating green fallow into crop rotations as a natural source of organic matter, essential for sustaining chernozem fertility and ensuring the resilience of agricultural production in the Southern Steppe of Ukraine. Keywords: southern chernozems, humus, biomass, balance, short-rotation crop rotation, cover crops.